Pulsatile Femoral Vein Doppler and Congestive Delirium, What Is the Relationship?: A Case Report. Issue 10 (18th October 2022) - Hammoud, Ali; Saade, Elena; Jarry, Stéphanie; Baelen, Sophie; Couture, Etienne J.; Beaubien-Souligny, William; Denault, André Y.
Abstract : Delirium is common in patients undergoing cardiac surgery, and venous congestion has been reported as an important risk factor. We report a 69-year-old patient who developed postoperative delirium in the intensive care unit following aortic valve replacement surgery. The postoperative course was complicated by delirium for which echographic signs of venous congestion on the portal and the renal but also the femoral veins and their resolution correlated with the course of delirium. The use of common femoral vein Doppler as a simple bedside technique to predict and identify congestive delirium has not been reported before.